Working until you drop: Image concerns or prosocial motives? - Hande Erkut; Shaul Shalvi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
Working hard is costly, so people should work wisely. Yet, they do not always work efficiently, spending their effort on tasks that do not bring tangible benefits. One reason that potentially amplifies inefficient working is that people work in social environments where they are observed and where others' earnings also depend on their effort. In this paper, we investigate whether people work and earn more than they need, and if so why? We use laboratory experiments to disentangle two concerns that potentially lead people to work inefficiently hard, namely image concerns and prosocial motives. Our results suggest that people indeed overwork unnecessarily, and that this is mainly due to image concerns.
Keywords: C91; D91; J22; 330; overworking; image concerns; social preferences